Threats to Indonesia’s Economic Sovereignty in the Appointment of Foreign Executives in State-Owned Enterprises - Elizatul Mufidah Indana; Ibnu Alwaton Surya Waliden; Abdelmajid Idris Mohammed Khalil; Dominikus Rato; Y. A. Triana Ohoiwutun (Indonesian Journal of Law and Islamic Law (IJLIL), 2025)
This study examines the constitutional implications of the government policy that allows foreign nationals to occupy executive positions in State-Owned Enterprises (SOEs) concerning the principle of national economic sovereignty, as stipulated in Article 33 of the 1945 Constitution of the Republic of Indonesia. The background of this research lies in the growing practice of economic globalization, which demands efficiency and professionalism in SOE management but potentially shifts the meaning of state control over vital sectors of production. This study employs a normative juridical method with conceptual and comparative approaches to national regulations and international practices. The findings indicate that the involvement of foreign nationals in SOE management can be acceptable insofar as it is limited by constitutional principles, the nationality principle, and strict public oversight. The novelty of this research lies in proposing a constitutional policy model that integrates corporate efficiency with state economic sovereignty. This model has practical implications for the international community: positively, it provides a clear legal framework for global investors and professionals, thereby enhancing the predictability of the investment climate and offering an adaptive model for other developing countries to align world-class corporate governance with national sovereignty; however, potentially negatively, strict limitations might be perceived by the global business community as a barrier or discrimination against the transfer of expertise and international capital flows. This integrative approach remains rarely discussed in the field of constitutional economic law in Indonesia.